975. Dalbavancin for the Treatment of Vertebral Osteomyelitis. (15th December 2022) - Streifel, Amber C; Strnad, Luke; Sukerman, Ellie; Makadia, Jina T; Lewis, James S; Douglass, Alyse H; Young, Kathleen; Mayer, Heather; Sikka, Monica K
Abstract: Background: Dalbavancin (DAL) provides an alternative to daily intravenous (IV) antibiotics for the treatment of infections when treatment in the outpatient setting is not practical. While clinical outcomes data for the treatment of osteomyelitis (OM) with dalbavancin has expanded, data specifically addressing vertebral OM remains limited. Methods: We conducted a retrospective single center study to evaluate DAL use at our institution for patients with vertebral OM, including relevant treatment details and follow-up to 90 days post last DAL dose. All patients aged> 18 years who received at least one dose of DAL between 2015 and 2021 via medication records were included. Results: Twenty-eight patients with vertebral OM (24 with native vertebral OM) were treated with DAL for at least a portion of a treatment course. The most commonly isolated organisms were methicillin-resistant Staphylococcus aureus (MRSA) (10; 35.7%) and methicillin-sensitive S. aureus (MSSA) (7; 25%). Cultures were negative for 7 patients (25%). Eight (28.5%) patients were bacteremic upon presentation, 5 (17.8%) with MRSA, 2 (7.1%) with MSSA, and 1 (3.6%) due to Enterococcus faecalis . All included patients had a history of substance use and 18 (64.2%) endorsed injection use. DAL was most commonly selected due to a history of injection drug use (19, 67.9%), lack of a safe home environment (6, 21.4%) or prior non-adherence to outpatient antibiotics (5, 17.9%). For the 11 patients who received one dose of 1500 mg, the mean duration of antibiotics prior to DAL was 29.3 days, 2 of these patients were intended for 2 dose regimens but did not complete a second dose. For the 17 patients who received 2 doses of 1500 mg, mean duration of antibiotics prior to DAL was 13.8 days. Adverse reactions were documented for 7 patients (25%), most commonly infusion reactions. Readmission for any reason at 30 days occurred for 1 patient (3.6%) and 2 patients (7.1%) at 90 days. Mortality at days 30 and 90 post-treatment were 0. Recurrence or relapse of infection at 30 and 90 days occurred for 1 (3.6%) patient each. Conclusion: DAL appears to be safe and well-tolerated for the treatment of vertebral OM, although clinical data comparing it to standard of care regimens, especially for vertebral OM due to S. aureus is needed before it can be recommended as standard of care. Disclosures: James S. Lewis, PharmD, FIDSA, Cidara: Advisor/Consultant|Merck: Advisor/Consultant|SeLux Diagnostics: Advisor/Consultant Monica K. Sikka, MD, F2G: Site research investigator.